Revealing the potent probiotic properties and alcohol degradation capabilities of Lactiplantibacillus plantarum BGI-J9 by combining complete genomic and phenotypic analysis - Fan, Yaqi; Ma, Zhihui; Wei, Benliang; Wen, Yangfeng; Xu, Xiaowei; Rao, Xing; Wu, Zhinan; Liu, Yanhong; Zhang, Haifeng; Zhong, Yiyi; Zou, Yuanqiang; Xiao, Liang (Frontiers in Microbiology, 2025)
Probiotics have demonstrated broad prospects in maintaining human health, and complete genome analysis enables unveiling the intrinsic probiotic mechanisms. In this study, the probiotic properties of Lactiplantibacillus plantarum BGI-J9 (BGI-J9) were explored via integrating complete genomic and phenotypic analysis. Results indicated that the high-quality complete genome of BGI-J9 comprises 3,128,867 bp with 2,926 coding sequences and an average GC content of 45%. Genomic annotation analysis revealed that BGI-J9 harbored nhaK, plsC, pyk, atp, opp, rps, rpl, rpm system genes, as well as plantaricin, glutathione peroxidase family, glutathione, catalase, thioredoxin encoding genes, and exhibited favorable gastrointestinal tolerance, antimicrobial activity, antioxidant activity in in vitro assays. Notably, alcohol degradation enzyme genes were identified in the BGI-J9 genome, which accounted for the potent in vitro alcohol dehydrogenase and acetaldehyde dehydrogenase activities and alcohol degradation capacity exhibited by BGI-J9. These findings indicated that BGI-J9 has the potential to assist in promoting alcohol degradation and mitigating alcohol-induced damage. In conclusion, this study first presented the complete genome of BGI-J9, furnishing a theoretical basis for its application in alleviating alcohol damage.